Conceptions of God, Freedom, and Ethics in African American and Jewish Theology - Buhring, K. author. aut Link
X, 262 p.
Keywords: This book is a consideration of major contemporary Black and Jewish understanding of God, examining how profound faith in a just God is sustained, and even strengthened, in the face of particularly horrific and long-standing evil and suffering in a community.